The effect of increasing the percentage of hydrogen added to methane in direct injection spark ignition engine to the composition of CO and CO2 emissions - Mansor, M.R.A.; Hoo, C.L.; Taib, N.M.; Aizon, W.G.W.; Ilham, Zul (Asian Research Publishing Network, 2017)
The emission of CO2 has been dramatically increased within the last decade and is still increasing each year, making it the main cause of global warming. CO2 is mainly created by burning fossil fuels such as petrol and diesel. One of the solutions to decrease the emission is by changing the use of petrol to alternative fuel such as Compressed Natural Gas (CNG) or hydrogen. CNG is primarily composed of methane and also contains ethane, propane and heavier hydrocarbons. Even though natural gas has the lowest carbon emission of all fossil fuel, it still has significant carbon content. On the other hand, hydrogen has no carbon content so the replacement of some percentage of natural gas to hydrogen will reduce carbon emission. This study was carried out in order to investigate the influence of increasing the percentage of hydrogen, as a substitute to methane, to the emission produced in the direct injection internal combustion engine conditions. The combustion of hydrogen-methane mixture was simulated by using Star-CCM+ CFD software. The design of the combustion chamber used is similar to the condition for the combustion of petrol in an internal combustion engine where all the valves were closed. The emission of CO and CO2 from the combustion was observed. The emission results of the percentage of hydrogen added to methane fuel was analysed and discussed. The results showed a decrease of carbon monoxide and carbon dioxide emissions with the increase of hydrogen percentage. This shows that hydrogen-methane mixture has a high potential to be used as the alternative combustion strategy in transportation to replace the existing nonrenewable fuels and potentially able to reduce the greenhouse gas problem.